Proceedings of the 2013 Conference on Internet Measurement Conference 2013
DOI: 10.1145/2504730.2504769
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis of a large ISP

Abstract: We present a time-series analysis of Cogent's inter-continental network. The analysis is based on descriptions of Cogent's routers and their interfaces, collected each week for more than one year. These descriptions are collected from public reverse DNS records, which we cross-validate using iffinder, a full Internet scan, and limited ground truth data provided by Cogent. For example, our dataset, which we make available to the research community, shows that while the number of Cogent routers grew by approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In 2013, Ferguson et al studied the interconnection, capacity, geography, and growth of Cogent's network. They continuously resolved the hostnames of address space used by Cogent to number their routers, and then applied a regex that they manually constructed to Cogent's hostnames to extract interface speeds, locations, and names of Cogent's routers [7]. They found that Cogent's network grew by 11 routers per week between 2012 and 2013.…”
Section: Extracting Information From Dnsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Ferguson et al studied the interconnection, capacity, geography, and growth of Cogent's network. They continuously resolved the hostnames of address space used by Cogent to number their routers, and then applied a regex that they manually constructed to Cogent's hostnames to extract interface speeds, locations, and names of Cogent's routers [7]. They found that Cogent's network grew by 11 routers per week between 2012 and 2013.…”
Section: Extracting Information From Dnsmentioning
confidence: 99%
“…Researchers have traditionally manually derived regular expressions (regexes) from apparent router naming conventions to extract network topology information, such as the geographic placement and roles of routers, link speeds, and router names (e.g., [6,7,27]). In this paper, we consider the challenge of automatically learning if an operator uses a convention within a suffix that includes a router name -i.e., a unique router identifier -by evaluating automatically generated regexes.…”
Section: Introductionmentioning
confidence: 99%
“…POPsicle finds 2.4x more physical nodes than Ark probes, and in our custom deployment in Chicago, POPsicle finds nearly all POPs identified in the Atlas physical topologies. In a case study of Cogent's network, POPsicle identified more than 90% of the POPs known through Atlas as well as through the recently described technique based on using reverse DNS records [21]. Moreover, it found many more POPs than Ark probes, or the most recent Rocketfuel measurements.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…To validate this idea, we deployed POPsicle at the Equinix IXP in Chicago, USA, and measured the number of POPs for 10 ISPs and found that POPsicle reveals almost all POPs compared to Atlas and extra POPs (in certain cases) compared to Ark. We also find through a case study of Cogent network that POPsicle identifies over 90% of the nodes identified in Atlas or by the reverse DNS technique of [21], compared with about 65% of the POPs identified through Ark, and only 25% identified in the most recently available Rocketfuel data.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation